Lightning runes - Turtledove, Harry (City of shadows, 2026)
Hardboiled Noir meets Urban Fantasy in a post-WWII Los Angeles where vampires, zombies, and demons are part of the social fabric. Magic is just another way to get killed in the City of Angels. Los Angeles, 1940s. The war is over, but the shadows are growing teeth. In this gritty Historical Urban Fantasy, detective work requires more than a badge and a .38. It requires an understanding of the runes that thrum beneath the pavement. It started with a knock on the door. It usually does. Now there's a body, a missing musician, and a trail of magic that smells like ozone and bad luck. The LAPD is out of its depth. The "square" world is waking up to a reality they aren't prepared to handle. Between the smoky jazz clubs of Central Avenue and the grease-stained floors of neighborhood garages, a new kind of power is rising. It's electric. It's ancient. And in the wrong hands, it's a death sentence for the whole city.